High Adiposity Is Associated With Higher Nocturnal and Diurnal Glycaemia, but Not With Glycemic Variability in Older Individuals Without Diabetes - Noordam, Raymond; Huurman, Neline C.; Wijsman, Carolien A.; Akintola, Abimbola A.; Jansen, Steffy W. M.; Stassen, Stephanie; Beekman, Marian; van de Rest, Ondine; Slagboom, P. Eline; Mooijaart, Simon P.; van Heemst, Diana (Frontiers in Endocrinology, 2018)
Background: It is well-known that adiposity is a risk factor for insulin resistance and type 2 diabetes mellitus. In the present study, we aimed to investigate the associations of measures of adiposity with indices of glycaemia and of glycaemic variability over a 72-hour period in nondiabetic older adults. Methods: This cross-sectional study was conducted in nondiabetic individuals from the Active and Healthy Ageing Study (N = 228), Switchbox (N = 116), and the Growing Old Together Study (N = 94). Body mass index (BMI) and waist circumference were measured, and indices of glycaemia and glycaemic variability were derived from continuous glucose monitoring (CGM) using the Mini-Med® CGM system. Associations between adiposity and CGM were studied separately for the three cohorts, and derived estimates were subsequently meta-analysed. Results: After meta-analysing the results from the separate cohorts, individuals with a higher BMI had higher levels of glycaemia. Individuals with BMI between 30 and 35 kg/m2 had 0.28 mmol/L (95% confidence interval [CI]: 0.12-0.44) higher 72h-mean glucose concentration, 0.26 mmol/L (0.10-0.42) higher diurnal glucose (6 – 0 AM), and 0.39 mmol/L (0.19; 0.59) higher nocturnal glucose (3 – 6 AM) than participants with a normal weight (BMI 18.5-25 kg/m2). However, no associations were observed between higher BMI and glycaemic variability. Results for glycaemia and glycaemic variability were similarly observed for a high waist circumference. Conclusions: High adiposity associates with constant higher mean glucose levels over the day in nondiabetic older adults.